ANALISIS STRATEGI PENGEMBANGAN POTENSI ANAK BERBAKAT DALAM PROSES PEMBELAJARAN DI SMPN 1 PANGARENGAN - Muessah Muessah; Fatimah Dwi Rahmayani; Erlina Damayanti; Mohammad Al Farisi; Jatim Desiyanto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Gifted children possess intellectual abilities, creativity, and learning potential that are above average compared to their peers, requiring educational services that are aligned with their needs and characteristics. However, learning in schools is still often conducted through conventional classroom instruction, which does not fully accommodate differences in students’ abilities, resulting in the potential of gifted children not being optimally developed. This study focuses on strategies for developing the potential of gifted children during the learning process at SMPN 1 Pangarengan, including the learning strategies implemented by teachers, the role of teachers, the forms of potential developed, as well as the challenges encountered and efforts to overcome them. This study employed a qualitative approach with a case study design conducted in Class VII-A of SMPN 1 Pangarengan, involving a subject teacher as the research participant. Data were collected through observation, in-depth interviews, and documentation, and were analyzed through data reduction, data presentation, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings indicate that teachers implemented differentiated instruction, Project-Based Learning (PjBL), inquiry-based learning, enrichment programs, and peer tutoring, which contributed to developing gifted students’ creativity, critical thinking, learning engagement, and deeper understanding of learning materials. Teachers also served as motivators, mentors, and facilitators. Despite challenges such as differences in students’ abilities, limited instructional time, inadequate learning facilities, and the absence of specialized programs for gifted students, teachers addressed these challenges through adaptive and innovative learning strategies. Therefore, student-centered learning tailored to students’ characteristics plays an important role in optimizing the academic and non-academic potential of gifted children. ABSTRAK Anak berbakat memiliki kemampuan intelektual, kreativitas, dan potensi belajar di atas rata-rata teman sebayanya sehingga memerlukan layanan pembelajaran yang sesuai dengan kebutuhan dan karakteristiknya. Namun, pembelajaran di sekolah masih cenderung dilaksanakan secara klasikal sehingga perbedaan kemampuan peserta didik belum sepenuhnya terakomodasi dan potensi anak berbakat belum berkembang secara optimal. Penelitian ini berfokus pada strategi pengembangan potensi anak berbakat dalam proses pembelajaran di SMPN 1 Pangarengan, meliputi strategi pembelajaran yang diterapkan guru, peran guru, bentuk potensi yang dikembangkan, serta hambatan dan upaya mengatasinya. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus yang dilaksanakan di kelas VII-A SMPN 1 Pangarengan dengan subjek seorang guru mata pelajaran. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi, kemudian dianalisis melalui tahap reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data diuji melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa guru menerapkan pembelajaran berdiferensiasi, Project-Based Learning (PjBL), pembelajaran berbasis inkuiri, program pengayaan, dan tutor sebaya yang berkontribusi terhadap pengembangan kreativitas, berpikir kritis, keaktifan belajar, dan pemahaman materi siswa berbakat. Guru berperan sebagai motivator, pembimbing, dan fasilitator. Meskipun terdapat hambatan berupa perbedaan kemampuan siswa, keterbatasan waktu, sarana pembelajaran, dan belum tersedianya program khusus, guru mengatasinya melalui strategi pembelajaran yang adaptif dan inovatif. Dengan demikian, pembelajaran yang berpusat pada siswa dan disesuaikan dengan karakteristik peserta didik berperan penting dalam mengoptimalkan potensi anak berbakat pada aspek akademik maupun nonakademik.